Rethinking childhood - Pufall, Peter B.; Unsworth, Richard P. (Rutgers University Press, 2004)
In Rethinking Childhood, twenty contributors, coming from the disciplines of anthropology, government, law, psychology, education, religion, philosophy, and sociology, provide a multidisciplinary view of childhood by listening and understanding the ways children shape their own futures. Taken together, these essays develop a new paradigm for understanding childhood as children experience these years. This paradigm challenges readers to develop fresh ways of listening to children's voices that enable both children and adults to cross the barriers of age, experience, and stereotypi.
Keywords: Children.; Children -- Social conditions.; Enfants -- Conditions sociales.; SOCIAL SCIENCE -- Children's Studies.; Children; Children -- Social conditions; Samfundsvidenskab -- Sociologi.